On the mean-field limit of consensus-based methods - Koß, Marvin; Weissmann, Simon; Zech, Jakob (Mathematical methods in the applied sciences, 2025)
Consensus-based optimization (CBO) employs a swarm of particles evolving as a system of stochastic differential equations (SDEs). Recently, it has been adapted to yield a derivative free sampling method referred to as consensus-based sampling (CBS). In this paper, we investigate the “mean-field limit” of a class of consensus methods, including CBO and CBS. This limit allows to characterize the system's behavior as the number of particles approaches infinity. Building upon prior work that carried out this analysis for other algorithms, we establish the existence of a unique, strong solution for these finite-particle SDEs. We further provide uniform moment estimates, which allow to show a Fokker–Planck equation in the mean-field limit. Finally, we prove that the limiting McKean–Vlasov-type SDE related to the Fokker–Planck equation admits a unique solution.